Determining Influence Of Teacher’s Workload On Academic Performance In Secondary Schools, Suba Sub-County Kenya - Rose, Adika Berda; Sika, James Ochieng (Advances in Social Sciences Research Journal, 2019)
Education all over the world is regarded as key to overall national development as it improves productive capacity of its citizens. Academic performance in terms of grades and mean score may be a yardstick propelling students from secondary schools to acquire university education. Teachers play a significant role towards academic performance and therefore their workloads may affect academic performance. In Suba Sub – County, in the period 2012 – 2015 percentage pass in KCSE was 36.2%, 26.46% and 36.76% while the mean grade was 4.6, 4.7 and 3.9 respectively. The neibouring sub – county performance was higher in terms of students with C+ and above and the mean grade respectively. The objectives of the study was to determine the influence of teacher workload on student’s academic performance in secondary schools in Suba Sub-County. The study used descriptive and Correlation survey design. The Study population comprise 33 secondary schools with 33 Head teachers, 164 teachers and 1,035 form four students. Stratified sampling was used to determine sample size which comprised of 311 form four students 49 teachers and 30 head teachers in the four existing zones; Kigoto, Gwassi, Kiabuya and Central. The study revealed that influence of teacher’s workload on academic performance was significant (r = .523, N = 154, p<0.01) and also that for every one unit increase teacher workload, there was a decrease in pupils academic achievement as signified by the coefficient (- .558). The study concluded that it is important to reduce workload with tighter control in monitoring attendance to teacher’s in classroom. The study recommended that all stakeholders be involved in enhancing students academic performance and the teachers’ observe best practices in performance of their duties.